Examining the Parallel Multiple Mediating Roles of Psychopathological Symptoms in the Relationship Between Childhood Traumas and Attitudes Towards Crime - Erbay, Ayhan (The Bulletin of Legal Medicine, 2024)
Objective: To analyze whether psychopathological symptoms have a mediating effect on the relationship between childhood traumas and criminal attitudes. Methods: In order to achieve the purpose, the correlational survey model was used, and a total of 391 people over the age of 18 participated online in this study covering the dates January 2023-January 2024 with the convenience sampling technique. Psychopathological symptoms in the relationship between childhood traumas and attitudes towards crime were examined with parallel multiple mediating variable analysis. Results: It was observed that childhood traumas did not have a direct effect on attitudes towards crime. Similarly, when childhood traumas were controlled and the effects of psychopathological symptoms on attitudes towards crime were examined, it was determined that no psychopathological symptom had a direct effect on attitudes towards violence, but interpersonal sensitivity and hostility symptoms had the possibility of indirectly strengthening the relationship. Conclusion: It was concluded that attitudes towards crime emerged as a result of the effects of the family, neighborhood and society on the individual rather than a mechanism triggered by individual characteristics or experienced traumas, and that psychopathological characteristics or past traumas trigger the tendency towards crime only if social conditions are appropriate.